Adaptive Reuse of Existing Buildings: Contemporary Relevance - Dotel, Nischal (Journal of Science and Technology, 2024)
Adaptive Reuse (AR) is an act of repurposing the existing buildings by making changes in the architecture accordingly. It is one of the most efficient construction techniques. This paper aims to conclude the contemporary relevance of this method in terms of sustainability. Several implications of repurposing around the world have been studied to come up with a better understanding of AR. Based on the case study of several repurposed buildings, and a site observation the relevance and suitability of this method is concluded in this paper. The process of Adaptive Reuse can be even more efficient if several factors are considered. Maintaining the originality of buildings by using similar materials and renovating buildings to match the original theme of the buildings can help to preserve the historic architectural value along with meeting contemporary requirements. Proper structural treatment should also be applied to further increase the lifespan of the building. The structural treatment may include adding new structural members or repairing the existing ones. With the help of a qualitative research methodology, this study focuses on the examination of the overall relevance of Adaptive Reuse as a sustainable approach to civil engineering constructions.